2014
DOI: 10.1021/jp409969g
|View full text |Cite
|
Sign up to set email alerts
|

Electron Localization of Polyoxomolybdates with ε-Keggin Structure Studied by Solid-State 95Mo NMR and DFT Calculation

Abstract: We report electron localization of polyoxomolybdates with ε-Keggin structure investigated by solid-state (95)Mo NMR and DFT calculation. The polyoxomolybdates studied are the basic ε-Keggin crystals of [Me3NH]6[H2Mo12O28(OH)12{MoO3}4] · 2H2O (1), the crystals suggested to have a disordered {ε-Mo12} core of [PMo12O36(OH)4{La(H2O)2.75Cl1.25}4]·27H2O (2), and the paramagnetic Keggin crystals of [H2Mo12O30(OH)10{Ni(H2O)3}4] · 14H2O (3). The spectra of (95)Mo static NMR of these samples were measured under moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…On the basis of 95 Mo NMR and DFT calculations, Nishimura and coworkers have concluded that electron density in this POM remains delocalised. 91 This implies that redox processes may populate/depopulate the Mo−Mo bonding in ε-Keggin, however, without inducing symmetry break, which is needed when considering its role as a node in a highly symmetrical framework structure. On the other hand, multielectron reductions in the α-Keggin lead to the formation of metal bonding within localised {Mo3} triads, that This journal is © The Royal Society of Chemistry 20xx…”
Section: Homometallic Metal−metal Bonding Between Addenda Centresmentioning
confidence: 99%
“…On the basis of 95 Mo NMR and DFT calculations, Nishimura and coworkers have concluded that electron density in this POM remains delocalised. 91 This implies that redox processes may populate/depopulate the Mo−Mo bonding in ε-Keggin, however, without inducing symmetry break, which is needed when considering its role as a node in a highly symmetrical framework structure. On the other hand, multielectron reductions in the α-Keggin lead to the formation of metal bonding within localised {Mo3} triads, that This journal is © The Royal Society of Chemistry 20xx…”
Section: Homometallic Metal−metal Bonding Between Addenda Centresmentioning
confidence: 99%
“…At high magnetic field, the CSA is enhanced, while the effects of the second‐order quadrupolar interaction are reduced. Among the several contributions reported for solid‐state 95 Mo NMR, only two deal with POMs . A couple of papers also deal with solid‐state 183 W NMR .…”
Section: Introductionmentioning
confidence: 99%
“…83,84 If only insulating diamagnetic compounds are taken into account, this range is reduced from −1885 ppm for the tricarbonyl(mesitylene)molybdenum to +2181 ppm for (NH 4 ) 2 MoS 4 . 67,70 To our knowledge, only 14 publications deal with determination of the 95 Mo chemical shift anisotropy (CSA) parameters 62,64,[66][67][68][69][70][71][72][73][74]80,90,91 and only one with the absolute orientation of the CS and electric field gradient (EFG) tensors. 69 Maximum values of 1010/1018 ppm (±5) and 7.8 MHz have been observed for the 95 Mo CSA and quadrupolar coupling constant in MoS 2 and MoO 2 , respectively.…”
Section: ■ Introductionmentioning
confidence: 99%